Reducing the risk of Dengue with Proper Diagnosis, Treatment and Education of People - Sakure, Sunita; Bhosale, Sarika; Shewale, Swapnil (International Journal of Medical Research and Review, 2015)
Aedes aegypti is known to play a significant role in the transmission of various dreadful diseases such as dengue fever, chikungunya and yellow fever. Dengue fever (DF) is primarily caused by dengue fever virus (DENV). As per state health department report released in May, 2014 Maharashtra has reported 722 cases of dengue this year accounting for 25% of the dengue cases around the country. DENV serotypes are majorly transmitted by infected female mosquito that takes a blood meal from an infected person with DF. During the initial 2–10 day febrile period, DENV spreads within the body of the mosquito infecting the gut lining and later to salivary gland. Mosquito lay their eggs in artificial and natural stagnant water containers. When an infected female mosquito bites a person the virus enters the skin with the mosquito’s saliva and infects leucocytes and reproduces inside these cells. The leucocytes respond by producing cytokines and interferons, causing high fever and severe pains. In severe infection, the virus invades organs like liver and bone marrow thereby lowering the blood pressure and internal bleeding leading to a risk of dengue hemorrhagic fever and dengue shock syndrome. Dengue NS-1 Antigen test is confirmatory for early and immediate diagnosis of dengue. The state of infection can be monitored by examination of platelet counts. As there is no antiviral drug discovered against dengue, so causing serious damage to people of all age groups. People should be educated and awareness should be carried out to overcome such a disease.